Dynamics of the Gut Bacteria and Fungi Accompanying Low-Carbohydrate Diet-Induced Weight Loss in Overweight and Obese Adults - Yu, Dan; Xie, Libin; Chen, Wei; Qin, Jin; Zhang, Jingjing; Lei, Min; Wang, Yue; Tang, Hongge; Xue, Sujuan; Liang, Xinxiu; Miao, Zelei; Xiao, Congmei; et al. (Frontiers in Nutrition, 2022)
Background: Low-carbohydrate (e.g., Atkins) dietary pattern is one of the most effective diets for weight loss, but little is known about the characteristics of the gut microbiota accompanying low-carbohydrate diets-induced weight loss. This study aims to profile dynamics of gut bacteria and fungi accompanying modified Atkins diets-induced weight loss among overweight and obese adults. Methods: Overweight and obese adults were screened to follow a modified Atkins diet plan (30% of energy from protein, 40% from carbohydrate and 30% from fat). We longitudinally profiled dynamics of gut bacteria and fungi based on 16S rRNA and ITS rRNA gene sequencing data, respectively. Results: A total of 65 participants followed the modified Atkins diets for 20-231 days, with 61 and 27 participants achieving a weight loss of at least 5% and 10%, respectively. Most of the participants who achieved 10% weight loss also experienced improvements on metabolic health. The diversity of gut bacteria and fungi increased after a weight loss of 5% and kept stable thereafter. Bacteria genera including Lachnoclostridium and Ruminococcus 2 from Firmicutes phylum were depleted, while Parabacteroides and Bacteroides from Bacteroidetes phylum were enriched after weight loss. The inter-kingdom analysis found an intensive covariation between gut fungi and bacteria, involving more than half of the weight loss-associated bacteria. Conclusions: This study confirmed the modulation of bacterial and fungal composition during weight loss with the low-carbohydrate diets and showed previously unknown links between intestinal bacteria and fungi accompanying the weight loss.